Thermoelectric modules built using ceramic legs grown by laser floating zone - Ferreira, N. M. (2022)
The present work reports thefirst attempt of thermoelectric module design, based on oxide materials grownthrough the laserfloating zone technique. Two modules with 4-legs thermoelectric were assembled usingBi2Ba2Co2Oyfibres as p-type legs, while Ca0.9La0.1MnO3and CaMn0.95Nb0.05O3fibres were used as n-type legs.Structural and electrical characterisation of the individualfibres was performed, and the results compared to theliterature. The evolution of open-circuit voltage on heating and cooling up to 723 K, present the expected trendsbased on the Seebeck coefficient of the individualfibres, suggesting good reliability of the modules duringtemperature cycling. The power generation performance was evaluated for a temperature difference up to 500 Kunder different electric loads. The maximum measured power was ~2.2 mW for a module volume of ~39 mm3.Nevertheless, the module here studies possess better performance than those commercially available.